2013
DOI: 10.26719/2013.19.5.474
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of food contamination with Listeria spp. in Kermanshah, Islamic Republic of Iran

Abstract: Listeria monocytogenes is a human pathogen causing serious diseases. We aimed to determine food contamination with Listeria spp. in Kermanshah, Islamic Republic of Iran. Samples (185 dairy, 187 meat products and 158 ready-to-eat foods such as salads) were randomly collected from markets. After processing, samples were cultured in half-Fraser and Fraser broth followed by cultivation on PALCAM and Oxford media. Confirmatory tests including carbohydrate utilization were performed on isolates to determine species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
2
6
3
Order By: Relevance
“…It should be noted that the contamination rate of Listeria in dairy products in our study was consistent with the results of [14]. A low level (1.1%) of L. monocytogenes contamination was found in soft cheese by [13]. Those results are different from the ones obtained in our study.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…It should be noted that the contamination rate of Listeria in dairy products in our study was consistent with the results of [14]. A low level (1.1%) of L. monocytogenes contamination was found in soft cheese by [13]. Those results are different from the ones obtained in our study.…”
Section: Discussioncontrasting
confidence: 57%
“…This could be due to preparing and processing minced meat (used, for example, in kebabs) in poor hygienic conditions Akya et al [13]. Although other factors such as equipment and food additives can also have a role in contamination, kebabs tend to be well cooked prior to consumption, reducing the chance of acquiring listeriosis in this kind of food Akya et al [13]. Our results showed differences when compared to other studies.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…It should be noted that the pathogenic L. monocytogenes in our research for the contamination rate of Listeria in dairy products, cheese are consistent with the results indicated by Jalali and his team [16]. A low level (1.1%) of L. monocytogenes contamination was found in soft cheese by Akya et al [15]. These results are not going with the current study.…”
Section: Discussionsupporting
confidence: 39%
“…The findings of these results indicated that the meat products were considerably more likely to be contaminated with L. monocytogenes than other food products. This could be due to the fact that preparation and processing of minced meat, like kebab, might be done in a poor hygienic condition [15]. Although other factors like equipments and food additives can also have a role in contamination, Kebab is well cooked before eating and thus reduces the chance of getting Listeriosis in this kind of food [15].…”
Section: Discussionmentioning
confidence: 99%